PENERAPAN PEMBELAJARAN MATEMATIKA DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENTS (TGT) UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR MATEMATIKA SISWA KELAS XI TSP SMK NEGERI 1 NGANJUK - AMROZI, AMROZI (Jurnal Teknologi Pendidikan dan Pembelajaran, 2014)
The purpose of this research are to: (1) To describe the application of mathematics learning with cooperative learning model Teams Games Tournaments (TGT) to increase the motivation to learn math class XI student of SMK Negeri 1 Nganjuk TSP. (2) To describe the application of mathematics learning with cooperative learning model Teams Games Tournaments (TGT) to improve learning outcomes math class XI student of SMK Negeri 1 Nganjuk TSP. This study is a qualitative research approach to action research. Data collection techniques through tests, interviews, documentation. The results showed: (1) The application ofÂ  TGT cooperative learning model to improve learning motivation in class XI student of SMK Negeri 1 TSP Nganjuk Semester I. It is evident from the increase in the percentage of students motivation began preliminary data 42.42 % to 61.49 % in the first cycle and 81.44 % in the second cycle. (2) The application of TGT cooperative learning model to improve learning outcomes in class XI student of SMK Negeri 1 TSP Nganjuk Semester I. It is evident from the increase in the percentage of students that mastery learning ranging from 45.45 % at baseline, became 72.73 % in the first cycle and the second cycle becomes 90.91%.Â Keywords: Mathematics, Cooperative Learning Model Type Teams Games Tournaments, Motivation to Learn, Learning Outcomes.